Bleomycin, vinblastine and dacarbazine combined with nonpegylated liposomal doxorubicin (MBVD) in elderly (≥70 years) or cardiopathic patients with Hodgkin lymphoma: a phase-II study from Fondazione Italiana Linfomi (FIL). Issue 12 (15th October 2019) - Salvi, Flavia; Luminari, Stefano; Tucci, Alessandra; Massidda, Stefania; Liberati, Anna Marina; Stelitano, Caterina; Zanni, Manuela; Re, Alessandro; Centurioni, Riccardo; Freilone, Roberto; Musuraca, Gerardo; Nassi, Luca; et al.
Abstract: This phase-II study assessed activity and toxicity of substituting conventional doxorubicin with nonpegylated liposomal doxorubicin in the conventional ABVD regimen for the treatment of elderly or cardiopathic patients with HL. Stage I–IIA and IIB–IV patients were treated with three courses of MBVD plus radiotherapy, or six courses of MBVD, respectively, plus radiotherapy limited to bulky or residual disease areas. The primary endpoints were CR rate and the rate of cardiac events. Forty-seven patients were enrolled. Median age was 75 years, 13 had stage I–II disease. Overall, CR was achieved by 36 patients (77%, 95% CI: 62–88), 100% and 68% in stage I–II and III–IV, respectively. With a median follow-up of 40 months (IQR: 36–45). Three-year overall survival (OS) and progression-free survival (PFS) were 70% and 43%, respectively. Cardiac events grades 3–5 were reported in two patients. In conclusion, MBVD's activity and safety profile was comparable to historical ABVD data. Trial registration: ClinicalTrials.gov identifier: NCT01523847.